The Experience Of Spiritual Self-care Among Malaysian Counsellors: An Exploratory Study - Nur Husna Mohd Hafiz; Muhammed Fauzi Othman; Mohd Zaliridzal Zakaria; Wan Mohd Fazrul Azdi Wan Razali; Nurhafizah Mohd. Sukor; Marina Munira Abdul Mutalib (Taylor & Francis Group, 2024)
This is a preprint article, it offers immediate access but has not been peer reviewed. Indexed by WOS/Scopus/ERA